DINAMIKA INTERAKSI SUKU TALANG MAMAK DI DESA TALANG PERIGI KECAMATAN RAKIT KULIM KABUPATEN INDRAGIRI HULU, RIAU - Bani, Bani; Zusmelia, Zusmelia; Anggreta, Dian Kurnia (Pendidikan Sosiologi, 2013)
Talang Mamak is tradition ethnic, Langkat Lama ethnic or Talang ethnic. The term of Talang ethnic means people who live in land and isolate in the forest. Seperated residence system, commoly occupy in left side of river with small house or hut. The research purposes to describe dynamics of Talang Mamak need fulfillment and describe the social interaction model between Talang Mamak ethnic and Malayan. The theory used in this research is symbolik interaksionisme theory by Herbert Blumer. The symbol that used in this research is symbolik that found on meaningful materials of Talang Mamak ethnic such as Bendul, Tonggap and also Talang Mamak interaction does action is suitable with the meaning. according to soekanto social interaction model consists of cooperation, competation, and conflict. This research uses descriptive tipe of qualitative approach. Technique of informan sorting done by using purposive sampling. Technique of data collection in this research used obsevation, intrview and documentation. Data analysis done in the research by using interactive by Miles and Huberman. In this research was found there happened food need fulfillment dynamics where to fulfill food, Talang Mamak provided by themself with moving field, but talang mamak donot do it anymore. talang mamak used clothes which also used bysociety commonly and Talang Mamak do not use clothes made from leaf or cloth (cawat) which only cover vital part of body. Then, Talang Mamak donot occupy in the forest but live at the edge of road. Interaction model that happrned between Talang Mamak and Malayan is cooperation in rubber sale, honey sale, cleaning worship place, and marriage tradition. Other interaction model happened between Talang Mamak and Malayan is threat conflict.